Radiografi Kepala Proyeksi AP dan Lateral pada Kasus Multiple Facial Bone Fracture Pasca Kecelakaan Lalu Lintas - Gibral Ulhaq; Nursama Heru Apriantoro (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2022)
Head Radiography in Emergency is a particular radiography procedure on the head that is used to analyze bones of the head as quickly and precisely as possible especially on patients post-accident. This research aims to analyze head radiography procedure with AP and Lateral projection and its use to diagnose Multiple Facial Bone Fracture post traffic accident. This research is a case study on one patient with the age of 35 at a hospital in the DKI Jakarta zone in August 2018. The imaging has been done using the Ysio Siemens X-ray machine and CR radiology cassette, with 78 kilovolts, 200 milliamperes, and 0,04 second of exposure factor. The result shows images of the head with the projection of AP and Lateral and shows the whole structure of bones within the head. The conclusion of this research is that the emergency imaging of the head was the most common procedure at the emergency department but it must be done as quickly and precisely as possible and show as it is not as it should be.Keywords: AP; lateral; fractureABSTRAK Radiografi kepala pada kasus gawat darurat  adalah pemeriksaan radiologi khusus untuk kepala yang digunakan untuk menganalisis tulang kepala pasien secara cepat dan tepat terutama pada kasus pasien pasca kecelakaan. Penelitian ini bertujuan untuk mengkaji pemeriksaan radiografi kepala dengan proyeksi AP dan Lateral dan kegunaannya dalam mendiagnosis pasien dengan klinis Multiple Facial Bone Fracture pasca kecelakaan lalu lintas. Penelitian ini merupakan studi kasus dengan satu pasien usia 35 tahun di salah satu rumah sakit di wilayah DKI Jakarta pada bulan Agustus 2018. Penggambaran dilakukan dengan menggunakan pesawat sinar X Siemens tipe Ysio dan kaset radiologi CR, dengan faktor eksposi 78 kilovolt, 200 miliampere, dan 0,04 detik. Hasil menunjukkan gambaran kepala dengan proyeksi AP dan Lateral yang menamppilkan struktur tulang kepala secara keseluruhan.Kata kunci: AP; lateral; fraktur